The Quality Influence of Implementing Good Corporate Governance on Bank Return On Assets (ROA) - Hamzah Muchtar, Evan (AN NUR: Jurnal Studi Islam, 2024)
Since the 1970s, discourse has emerged to form a Sharia bank located in Indonesia. Around 1974, a national seminar on Indonesia's relations with the Middle East and in 1976, the Bhinneka Tunggal Ika Foundation and the Institute for the Study of Social Sciences (LSIK) jointly held an international symposium 1976 and discussed this topic. This type of research is quantitative research using secondary data in the form of time series in the form of published Annual Reports and Good Corporate Governance Reports of Sharia Commercial Banks. The population in this research is 13 Sharia Commercial Banks. The sampling technique used was purposive sampling, and 11 Sharia commercial banks were obtained. The methods used are descriptive analysis, hypothesis testing using the coefficient of determination test, and partial t-test. The research results show no significant influence of Good Corporate Governance (GCG) on Return On Assets (ROA) in Sharia Commercial Banks in Indonesia for 2020-2022.